2016
DOI: 10.1152/ajprenal.00590.2015
|View full text |Cite
|
Sign up to set email alerts
|

Early development of podocyte injury independently of hyperglycemia and elevations in arterial pressure in nondiabetic obese Dahl SS leptin receptor mutant rats

Abstract: The current study examined the effect of obesity on the development of renal injury within the genetic background of the Dahl salt-sensitive rat with a dysfunctional leptin receptor derived from zinc-finger nucleases (SSmutant strain). At 6 wk of age, body weight was 35% higher in the SSmutant strain compared with SS rats and remained elevated throughout the entire study. The SSmutant strain exhibited impaired glucose tolerance and increased plasma insulin levels at 6 wk of age, suggesting insulin resistance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 109 publications
(147 reference statements)
4
33
0
Order By: Relevance
“…Although it is known that serum retinol concentrations are increased in patients with CKD, 48 scant data are currently available on the regulation of lipid and retinol metabolism in renal podocytes 46,47 . However, recent data suggest that podocytes can accumulate lipid droplets, and that this process is associated with activation of the inflammasome and is involved in the pathogenesis of glomerulopathy associated with T2DM and obesity 24,49‐51 . Consistently with decreased retinol bioavailability in pericytes carrying the PNPLA3 I148M variant, 43‐45 it has been reported that a highly selective agonist for retinoic acid receptor β2 (ie AC261) was able to ameliorate diabetic nephropathy in an experimental mouse model 52 .…”
Section: Discussionmentioning
confidence: 97%
“…Although it is known that serum retinol concentrations are increased in patients with CKD, 48 scant data are currently available on the regulation of lipid and retinol metabolism in renal podocytes 46,47 . However, recent data suggest that podocytes can accumulate lipid droplets, and that this process is associated with activation of the inflammasome and is involved in the pathogenesis of glomerulopathy associated with T2DM and obesity 24,49‐51 . Consistently with decreased retinol bioavailability in pericytes carrying the PNPLA3 I148M variant, 43‐45 it has been reported that a highly selective agonist for retinoic acid receptor β2 (ie AC261) was able to ameliorate diabetic nephropathy in an experimental mouse model 52 .…”
Section: Discussionmentioning
confidence: 97%
“…25,27 Williams' group generated an obese leptin and inulin insensitive model in the Dahl SS background which exhibits hypertension, euglycemia, hyperlipidemia, and massive renal damage on a 1% NaCl diet. 78,79 Further comparison of pressure-natriuresis sensitivity and sodium transporter activity in these models would help explore the differential hormonal regulation of sodium handling and water-electrolyte balance in polygenic cardiorenal conditions such as metabolic syndrome.…”
Section: (A) (B)mentioning
confidence: 99%
“…In the current study, proteinuria was already markedly elevated at baseline in SS LepR mutant rats compared to SS rats and had a tendency to decrease over the course of study. This result is not at all surprising, since we have previously observed that proteinuria declines after 14 weeks of age in the SS LepR mutant strain, which is more than likely due to a decline of renal function (McPherson et al, 2016). The impact of dylipidemia on the progression of proteinuria and decline in renal function is unclear but undoubtedly involves inflammation, oxidative stress, and lipid accumulation (D'Agati et al, 2016;Yang et al, 2017;Gai et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, the presence of dyslipidemia has been associated with a greater risk for the development of CKD (Kasiske et al, 1993;Guijarro and Keane, 1996;Keane, 2000). In support of this finding, preclinical studies have demonstrated similar results, in which glomerular injury and tubulointerstitial damage were markedly increased in the setting of dyslipidemia (McPherson et al, 2016(McPherson et al, , 2020. We have previously reported that the obese Dahl salt-sensitive leptin receptor mutant (SS LepR mutant) rat develops dyslipidemia, progressive proteinuria, and glomerular injury as early as 6 weeks of age independent of hyperglycemia and elevations in arterial pressure (McPherson et al, 2016(McPherson et al, , 2020.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation